Women for Women: Discourse Analysis of Female’s Political Discourse Supporting Women’s Issues (A Case Study of Queen Rania’s English Speeches) - Amaireh , Hanan (Dirasat: Human and Social Sciences, 2022)
The focus of this study is the area of discourse analysis. This study analyses the political discourse of Queen Rania of Jordan’s English speeches. The data of the study consist of the English speeches the Queen delivered from 2016 to 2018. This study examines whether her speeches draw on the characteristics of the ’Feminine Style’ of women’s political discourse in qualitative and quantitative analysis. The paper concludes that women in the political arena prioritise women’s issues and address them through using some rhetorical techniques such as storytelling in order to convince the audience to support them.